Effects of teacher explicit instruction in stance-taking on students’ perceptions of stance and on their academic writing beliefs - Zhang, Lu; Zhang, Lawrence Jun; Xu, Ting Sophia (Frontiers in Psychology, 2023)
Scholars have underscored the importance of raising students’ awareness and understanding of stance-taking in academic writing. However, studies on the effects of pedagogical intervention are just a few. To strengthen this line of inquiry, this paper reports on an intervention study with explicit instruction of stance metalanguage based on the SFL Engagement framework and its effects on EFL students’ perceptions of stance as well as on their writing beliefs. A treatment group (n = 26) and a comparison group (n = 24) were involved. An eight-week writing intervention was provided in the treatment group, while the comparison group received regular curriculum-based instruction. Data from multiple sources were collected prior to and after the writing intervention, including two five-point Likert-scale questionnaires, semi-structured interviews, and reflective journals, to examine possible changes in students’ self-reported perceptions of stance and writing beliefs. Results showed that the intervention was effective in enhancing students’ stance awareness and transactional writing beliefs. Qualitative results further revealed that while the comparison group retained a preference for tentative stance after the writing instruction, intending to avoid potential challenges from readers, the treatment group exhibited a shift in preference for assertive stance valuing strengths of claims. The treatment group further exhibited an inclination to adopt a wider range of stance options for various rhetorical purposes. Pedagogical suggestions are discussed.